2014
DOI: 10.1007/s10616-014-9821-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence based cell counting in collagen monolayer cultures of primary hepatocytes

Abstract: Accurate determination of cell number is essential for the quantitative description of biological processes. The changes should be related to a measurable reference e.g. in the case of cell culture, the viable cell number is a very valuable reference parameter. Indirect methods of cell number/viability measurements may have up to 10 % standard deviation. This can lead to undesirable large deviations in the analysis of ''-omics'' data as well as time course studies. Such data should be preferably normalized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…The specific binding of Aβ42 was calculated by subtracting the fluorescence of cells in the absence of Aβ42 from that of fluorescence in the presence of varying concentrations of Aβ42. The data were analyzed using Image J software as described in Priesnitz et al [26].…”
Section: Aβ-rage Interaction In Transfected Cell Linementioning
confidence: 99%
“…The specific binding of Aβ42 was calculated by subtracting the fluorescence of cells in the absence of Aβ42 from that of fluorescence in the presence of varying concentrations of Aβ42. The data were analyzed using Image J software as described in Priesnitz et al [26].…”
Section: Aβ-rage Interaction In Transfected Cell Linementioning
confidence: 99%
“…Other quality criteria included typical hepatocytes morphology with binucleated cells, cell contacts, and polarity which can be seen in cultures of both rat types irrespective of age groups. We used a previously described method to calculate the cell size . It was observed that the SD PRH were slightly larger in size (supplementary Table S6).…”
Section: Resultsmentioning
confidence: 99%
“…Cells were stained for 10 min with Calcein AM dissolved in WME in a final concentration of 4 μg/mL. The method for cell counting was established in our laboratory and is described in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations